2012
DOI: 10.1021/la204204j
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Characterization of Zein Self-Assembly

Abstract: Zein, a major protein of corn, is rich in α-helical structure. It has an amphiphilic character and is capable of self-assembly. Zein can self-assemble into various mesostructures that may find applications in food, agricultural, and biomedical engineering. Understanding the mechanism of zein self-assembly at the nanoscale is important for further development of zein structures. In this work, high-resolution transmission electron microscopy (TEM) images revealed nanosize zein stripes, rings, and discs containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
181
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(197 citation statements)
references
References 32 publications
8
181
0
8
Order By: Relevance
“…The previously mentioned results revealed that particle formation in this study may be different from the cases reported before, in which ethanol evaporation induced layer-by-layer adsorption of zein to a central core or nucleus. 39,40 The layer-by-layer assembly requires a long time and slow ethanol evaporation without stirring, and thus burst nucleation and uniform particle growth would be less likely to occur.…”
Section: Insight Into Formation Of Zein Nanoparticles Timescale Of Pamentioning
confidence: 99%
“…The previously mentioned results revealed that particle formation in this study may be different from the cases reported before, in which ethanol evaporation induced layer-by-layer adsorption of zein to a central core or nucleus. 39,40 The layer-by-layer assembly requires a long time and slow ethanol evaporation without stirring, and thus burst nucleation and uniform particle growth would be less likely to occur.…”
Section: Insight Into Formation Of Zein Nanoparticles Timescale Of Pamentioning
confidence: 99%
“…However, since the structure in mainly intramolecular (not intermolecular) with β-barrel domains and is very stable, it has been suggested that this could not contribute to the required protein-protein interactions . Figure 2 shows the model developed by Wang and Padua (2012) to explain how zein (α-zein) selfassembles into nanostructures during film formation through a change from α-helical to antiparallel β-sheet secondary structure. What has been proposed by Erickson et al (2012) for when zein is mixed with water into a dough clearly parallels this.…”
Section: Influence Of Secondary Structure On Dough Functionalitymentioning
confidence: 99%
“…Wang and Padua et al (10) recently described a possible nano-scale mechanism for the selfassembly of various zein mesostructures. The self-assembly of these zein structures appears to be driven by the amphiphilic nature of the protein and occurred when changes were made to the polarity of an aqueous ethanol solution of zein by evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of dissolving the protein in aqueous ethanol and increasing the polarity of the solution by evaporation of the ethanol, the kafirin is dissolved in a primary solvent, glacial acetic acid, water is then added resulting in the formation of kafirin microparticles (2). In both cases there is a change in solvent polarity, causing microparticle formation as described by Wang and Padua (10,11) for zein.…”
Section: Introductionmentioning
confidence: 99%